Introduction - Beatriz Contreras Tasso; Patricio Mena Malet (Études Ricoeuriennes / Ricoeur Studies, 2019)
Introduction (english version) of ERRS, 2018, 9, 2, “Affectivity, Initiative, Fragility and Vulnerability in Ricœur’s Philosophical Anthropology”